Sales and leases of goods - Meyer, Alfred W. (Black letter series, 1993)
Commercial Law: Definition, Scope, Parties, Types of Transactions, Sources; The UCC: History, Nature, Policies, Content, Code Methodology; Sale of Goods: Scope, Policies, Contract Formation, Offer, Acceptance, Statute of Frauds; Performance: General Obligations, Seller's Obligations, Buyer's Obligations, Risk of Loss, Excusable NonPerformance, Modification; Remedies: Breach of Contract, Seller's Remedies, Buyer's Remedies, Agreed Remedies, Statute of Limitations; Third Party Claims: Ownership, Security Interests; Creditors and Purchasers' Leasing of Goods: Scope, Policies, "True Lease, " Definitions, Choice of Law and Forum, Private Autonomy, Unconscionability, Statute of Frauds, Warranties, Transfer and Alienability, Priority Disputes, Fixture Claims, Sale and Leaseback, Finance Leases, Default by Lessor, Default by Lessee.